Implementasi Program Eco Masjid (Idarah, ‘Imarah, Ri’ayah) di Masjid Nur Muhammad Desa Randuagung Singosari Malang - Fifin Nikmatus Sholihah; Yeni Febrianti; Oktavia Dwi Saputri; M. Azkal Azkiya; Nova Arum Wahyuningtyas; Muhammad Idham Kholid; Rosidin (STAI Ma'had Aly Al-Hikam Malang, 2025)
Abstract The concept of Green Mosques (Ecomosques) in Indonesia remain an elitist issue and have not yet developed into a widespread and popular movement. Therefore, a collective effort is needed to realize this program, one of which is through community service activities. The community service method employed is Service Learning (SL) based on Kolb’s Experiential Learning model, which consists of Concrete Experience (CE), Reflective Observation (RO), Abstract Conceptualization (AC), and Active Experimentation (AE). The outcomes of this community service activity include the implementation of three work programs aligned with the functions of Idarah (administration and management), ‘Imarah (welfare and religious activities), and Ri’ayah (maintenance and facilities). First, assistance to the takmir (mosque management board) as a representation of the Idarah function, focusing on coordination, facilitation, and initiation by the service team to help ease managerial duties and responsibilities related to the ecomosque concept. Second, optimization of Majelis Ta’lim as a representation of the ‘Imarah function, emphasizing the active participation of the service team in consultation, socialization, and ecomosque education through Majelis Ta’lim sessions held after the Fajr and Maghrib prayers, discussing Qur’anic exegesis, creed (aqidah), jurisprudence (fiqh), and Sufism (tasawuf). Third, preservation of facilities and infrastructure as a representation of the Ri’ayah function, focusing on the active role of the service team in maintaining cleanliness, sanctity, health, and the aesthetic quality of the mosque in accordance with ecomosque criteria. Keywords: Ecomasjid; Idarah-‘Imarah-Ri’ayah, Service Learning, Mosque Caretaker. Abstrak Masjid Hijau (Ecomasjid) di Indonesia masih menjadi isu elitis, belum menjadi gerakan yang massif dan populis. Maka diperlukan gerakan bersama untuk mewujudkan program tersebut, dan salah satunya dengan kegiatan pengabdian kepada masyarakat. Metode pengabdian yang digunakan adalah Service Learning (SL) berbasis Experiential Learning model Kolb yang terdiri dari Concrete Experience (CE), Reflection Observation (RO), Abstract Conceptualization (AC) dan Active Experimentation (AE). Hasil kegiatan pengabdian ini adalah realisasi tiga program kerja yang sesuai fungsi Idarah (administrasi dan manajemen), ‘Imarah (kesejahteraan dan kegiatan), dan Ri’ayah (pemeliharaan dan fasilitas). Pertama, Asistensi Pengurus Takmir sebagai representasi fungsi Idarah yang difokuskan pada koordinasi, fasilitasi dan inisiasi tim pengabdi untuk membantu meringankan tugas dan tanggungjawab ketakmiran yang relevan dengan ecomasjid. Kedua, Optimalisasi Majelis Ta’lim sebagai representasi fungsi ‘Imarah yang difokuskan pada partisipasi aktif tim pengabdi untuk konsultasi, sosialisasi dan edukasi ecomasjid melalui Majelis Ta’lim ba’da Shubuh dan Maghrib yang membahas Tafsir Al-Qur’an, Akidah, Fikih dan Tasawuf. Ketiga, Pelestarian Sarana dan Prasarana sebagai representasi fungsi Ri’ayah yang difokuskan pada peran aktif tim pengabdi dalam menjaga kebersihan, kesucian, kesehatan dan keindahan masjid sesuai kriteria ecomasjid. Kata kunci: Ekomasjid; Idarah-‘Imarah-Ri’ayah; Pembelajaran Layanan; Takmir Masjid.